Reconstructing Ancestral Connections in the Sahara Using the COI Gene: The Role of Western Libyan Cerastes cerastes in Biodiversity Conservation and Forensic Identification - Tarek Shoieb (African Journal of Advanced Pure and Applied Sciences, 2026)
North African horned vipers (Cerastes cerastes) represent a widespread but poorly understood species complex across Saharan and Sahelian regions. Libya, despite its central geographic position, remains critically under-sampled in molecular phylogenetic studies of this group. Here we present the mitochondrial COI barcode sequence (621 bp) of a Cerastes cerastes specimen from the Nalut region (western Libya, near the Tunisian border). We compared this sequence to 11 conspecific sequences from Egypt, Chad, Niger, Mauritania, Morocco, and two outgroup species (Cerastes gasperetti, Cerastes vipera) using Maximum Likelihood (ML), Neighbor-Joining (NJ) phylogenetic reconstruction, Median-Joining network analysis, and pairwise genetic distances under the Kimura-2-parameter (K2P) model. Our results reveal that the Libyan Nalut specimen forms a strongly supported clade (bootstrap 99–100%) with populations from Morocco (Figuig and Oued Lakhchab) and Mauritania (Tiris Zemmour, Tagant, Trarza, Dakhlet-Nouadhibou), showing close genetic affinity (mean K2P distance 0.032–0.034). In contrast, the Libyan haplotype is genetically distant from Egyptian and Chadian populations (mean distance 0.045–0.063), suggesting a phylogeographic break coincident with the Libyan Desert and the Nile River corridor. The Median-Joining network demonstrated a novel haplotype in the Nalut region, which could indicate to cryptic diversity and potential local endemism. These findings could have direct implications for snake conservation in Libya, taxonomic revision of the Cerastes cerastes complex, and forensic identification. We strongly recommend expanded sampling across Libya’s diverse ecoregions to fully document the hidden genetic diversity in this understudied North African biodiversity hotspot.